Coaching Strategy-based for Raw Sweet Potato’s Small Medium Enterprise to be Leading in Payakumbuh - Hadi Irfani; Rina Mariana; Sitti Rizki Mulyani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2016)
The purpose of this study is to observe, interviews and collecting questionnaires regarding the provision of Small Medium Enterprise(SME) development strategy which can be made from Raw sweet potatoes SMEs in Payakumbuh.The method used in this study is a qualitative research method with a descriptive design, in which the data obtained in the form of words written or spoken of the people and observed behavior. The amount of sample 24 entrepreneurs, where sampling using purposive sampling technique. The research result is analyzed using SWOT analysis.The results showed that raw sweet potato entrepreneurs for SMEs in Payakumbuh city which is built on the service industry employers and trade provincial, district or city, able to be a driving force in the economic growth and development of the Payakumbuhcity. Judging from the characteristics of entrepreneurs based i.e.(1) Competence and commitment employers showed that employers have been trying to realize SMEs and superior quality, but has not been able to expand its business for the better because it is constrained by the lack of competence of the entrepreneurs themselves;(2) The aspects of coaching is based on the performance of the builder and the expectations of employers showed that employers expect to develop SME. Being an excellent business, but is not supported by the builder for a better performance in improving SMEs in all aspects.